Novel Methacrylate-Based Multilayer Nanofilms with Incorporated FePt-Based Nanoparticles and the Anticancer Drug 5-Fluorouracil for Skin Cancer Treatment - Kristijan Skok; Tanja Zidarič; Kristjan Orthaber; Matevž Pristovnik; Nina Kostevšek; Kristina Žužek Rožman; Sašo Šturm; Lidija Gradišnik; Uroš Maver; Tina Maver (MDPI AG, 2022)
Despite medical advances, skin-associated disorders continue to pose a unique challenge to physicians worldwide. Skin cancer is one of the most common forms of cancer, with more than one million new cases reported each year. Currently, surgical excision is its primary treatment; however, this can be impractical or even contradictory in certain situations. An interesting potential alternative could lie in topical treatment solutions. The goal of our study was to develop novel multilayer nanofilms consisting of a combination of polyhydroxyethyl methacrylate (PHEMA), polyhydroxypropyl methacrylate (PHPMA), sodium deoxycholate (NaDOC) with incorporated superparamagnetic iron-platinum nanoparticles (FePt NPs), and the potent anticancer drug (5-fluorouracil), for theranostic skin cancer treatment. All multilayer systems were prepared by spin-coating and characterised by atomic force microscopy, infrared spectroscopy, and contact angle measurement. The magnetic properties of the incorporated FePt NPs were evaluated using magnetisation measurement, while their size was determined using transmission electron microscopy (TEM). Drug release performance was tested in vitro, and formulation safety was evaluated on human-skin-derived fibroblasts. Finally, the efficacy for skin cancer treatment was tested on our own basal-cell carcinoma cell line.